2002
DOI: 10.1067/mva.2002.127527
|View full text |Cite
|
Sign up to set email alerts
|

Composite sequential grafts for femorocrural bypass reconstruction: Experience with a modified technique

Abstract: In the absence of sufficient autologous vein, patients needing bypass to crural arteries can be offered reconstruction with composite sequential grafting with satisfactory results. Furthermore, an occluded above-knee popliteal segment is not a contraindication for composite sequential bypass reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Interestingly, they found no difference in patency between composite grafts constructed from the arm or leg vein. 26 Several retrospective studies have shown that even alternative veins (other than GSV) have satisfactory patency rates. 3,4,10,11,15,18 Previously, the arm vein was usually used to perform very distal bypass in patients without GSV or as an alternative to preserve the contralateral GSV.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, they found no difference in patency between composite grafts constructed from the arm or leg vein. 26 Several retrospective studies have shown that even alternative veins (other than GSV) have satisfactory patency rates. 3,4,10,11,15,18 Previously, the arm vein was usually used to perform very distal bypass in patients without GSV or as an alternative to preserve the contralateral GSV.…”
Section: Discussionmentioning
confidence: 99%
“…Mahmood et al have described a composite synthetic and vein graft with spatulated ends, anastomosed with a side-to-side configuration, incorporated into an intermediate-level artery as a single anastomosis 10. This configuration showed promising results offering better compliance matching and with a reported 2-year patency rate of 73% 10.…”
Section: Discussionmentioning
confidence: 99%
“…This configuration showed promising results offering better compliance matching and with a reported 2-year patency rate of 73% 10. However this side-to-side anastomosis creates a deep reservoir with the potential for poor graft angulation at the intermediate site, thereby increasing turbulence and potentially affecting graft patency.…”
Section: Discussionmentioning
confidence: 99%
“…lnterestingly, they found no difference in patency between composite grafts constructed from the arm or leg vein. 26 Severa! retrospective studies have shown that even alternative veins ( other than GSV) have satisfactory patency rates.…”
Section: Discussionmentioning
confidence: 99%